Experience capitalization: Gathering information – team work and flexibility - Neupane, Hari Sharma (Technical Centre for Agricultural and Rural Cooperation, 2019)
I work as a Local Entrepreneurship and Institutional Development Consultant in the IFAD-sponsored Improved Seeds for Farmers Programme (KUBK-ISFP) in Nepal. Together with my colleague, Krishna Prasad Paudel, we joined the CTA-run training on experience capitalization in Goa, India. This has been a new way forward for us in reporting on our programmes.